2014
DOI: 10.1111/imr.12183
|View full text |Cite
|
Sign up to set email alerts
|

Directing traffic: IL‐17 and IL‐22 coordinate pulmonary immune defense

Abstract: Summary Respiratory infections and diseases are among the leading causes of death worldwide, and effective treatments likely require manipulating the inflammatory response to pathogenic microbes or allergens. Here we review mechanisms controlling the production and functions of interleukin-17 (IL-17) and IL-22, cytokines that direct several aspects of lung immunity. Innate lymphocytes (γδT cells, natural killer cells, innate lymphoid cells) are the major source of IL-17 and IL-22 during acute infections, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 181 publications
(249 reference statements)
2
147
0
1
Order By: Relevance
“…The role of Th17 in protection against viral infections is not clear: while some studies demonstrated their role in protection (32,33), others suggested no role (34) or even enhancement of viral infection (35). Development of Th17 cells was previously associated with pulmonary immune defense (36) or inflammation in chronic obstructive pulmonary disease and lung cancer (37). Modest amounts of GPspecific + or CD103 -CD8 + T cells were capable of CD107a mobilization.…”
Section: Respiratory Vaccination Induces a Greater Activation Of Cd8mentioning
confidence: 99%
“…The role of Th17 in protection against viral infections is not clear: while some studies demonstrated their role in protection (32,33), others suggested no role (34) or even enhancement of viral infection (35). Development of Th17 cells was previously associated with pulmonary immune defense (36) or inflammation in chronic obstructive pulmonary disease and lung cancer (37). Modest amounts of GPspecific + or CD103 -CD8 + T cells were capable of CD107a mobilization.…”
Section: Respiratory Vaccination Induces a Greater Activation Of Cd8mentioning
confidence: 99%
“…In mammals, IL17 ligand expression has been linked not only to protective immunity but also excessive tissue inflammation and damage in the gut and lungs. 83 Recent work by our group identified and characterized 7 IL17 ligands and 4 IL17 receptor (IL17R) homologues from transcriptomic and genomic databases of channel catfish. To gain insight into the mucosal actions of the IL17A/Fs-associated pathway in inflammatory processes, the expression profiles of 3 IL17A/Fs and their putative receptors IL17RA and IL17RC in mucosal tissues of catfish following experimental challenge with E. ictaluri and F. columnare were investigated.…”
Section: Soluble Mediators Of Inflammationmentioning
confidence: 99%
“…The major source for IL-17 and IL-22 during acute infection is innate lymphocytes (cd T-cells and natural killer cells). However, Th17 T-cells arising from maturation of CD4 helper cells contribute to cytokine production during induced immunity (23,28,30). Il-17 is key to iBALT formation (41) with or without the participation of dendritic cells (16).…”
Section: Il-17 and Il-22mentioning
confidence: 99%
“…IL-17 acts by increasing expression of chemokines CXCL12 and CXCL13, which are critical for follicle formation. IL-22 promotes epithelial proliferation (18,28), including epithelial cell transformation and tumorigenesis (21), through receptors on epithelial cells involved in STAT3 activation that are not found on immune cells (48 …”
Section: Il-17 and Il-22mentioning
confidence: 99%